Pengaruh Penggunaan Celebrity Endorser Arief Muhammad di Instagram Terhadap Brand Image Erigo Store - Setia Indah Setara Bulan; Ratih Hasanah Sudrajat (Sospol : Jurnal Sosial Politik, 2019)
In Indonesia there are already many popular local products market their products using social media, which one is in the fashion field, namely local t-shirts. The IDN Times article mentions there are 10 highly recommended local brands namely Erigo, Oomaoo, Sans, Monstore, Thanksinsomnia, Kamengski, Yogs, Sunday Sunday Co., Thinkcookcook, and Dreambirds Artwear. Erigo Store get first ranked with the number of Instagram followers 376.000 in September 2018 so Erigo Store as a local brand already has fans among the people of Indonesia. Seeing this phenomenon, it can be seen that brands have a very important role. To build the Erigo brand into a brand that can be trusted by the public, a strategy is needed to strengthen a brand, which one is through endorsement. To find out the effect of using Celebrity endorser on brand image, this research focus on examining Erigo. Purpose of this study to find the influence of celebrity endorser Arief Muhammad on Instagram Erigo brand image and how much affected partially. Method in this study is quantitative with type descriptive and causal research. Sampling technique using non-probability sampling method of purposive sampling, with respondents 100 people. Data analysis technique is descriptive analysis, classic assumption test, simple linear regression analysis, coefficient determination and hypothesis testing. The results of the t-test found the celebrity endorser had influence on the brand image. This is evidenced by thitung (9,918)> ttable (1,661). Based on result determination coefficient, celebrity endorser Arief Muhammad had an influence of 50.1% on the Erigo brand image.